Patient experience of negative effects of psychological treatment: results of a national survey. (March 2016) - Crawford, Mike J.; Thana, Lavanya; Farquharson, Lorna; Palmer, Lucy; Hancock, Elizabeth; Bassett, Paul; Clarke, Jeremy; Parry, Glenys D.
Abstract : Background: To make informed choices, patients need information about negative as well as positive effects of treatments. There is little information about negative effects of psychological interventions. Aims: To determine the prevalence of and risk factors for perceived negative effects of psychological treatment for common mental disorders. Method: Cross-sectional survey of people receiving psychological treatment from 184 services in England and Wales. Respondents were asked whether they had experienced lasting bad effects from the treatment they received. Results: Of 14 587 respondents, 763 (5.2%) reported experiencing lasting bad effects. People aged over 65 were less likely to report such effects and sexual and ethnic minorities were more likely to report them. People who were unsure what type of therapy they received were more likely to report negative effects (odds ratio (OR) = 1.51, 95% CI 1.22–1.87), and those that stated that they were given enough information about therapy before it started were less likely to report them (OR = 0.65, 95% CI 0.54–0.79). Conclusions: One in 20 people responding to this survey reported lasting bad effects from psychological treatment. Clinicians should discuss the potential for both the positive and negative effects of therapy before it starts.